Mandala and Support Ruler in Islamization on the North Coast of Java (Case Study of Mandala Sunan Bonang) - Fahmi, Muhammad Nabil (Proceeding International Conference on Religion, Science and Education, 2022)
Islamization in the nusantara began to experience acceleration in the 15th century AD when the saints, sunans, and another spreader of Islam used various da'wah approaches. One of the approaches used is the educational approach by acculturating the pre-Islamic education model called the mandala. Based on several archaeological findings and local historiographical sources such as manuscripts, many Islamic mandalas were developed by the Walisongo and their networks during this period. This study aims to reveal further the significance of the role of mandalas in the process of Islamization on the north coast of Java and the role of local rulers behind the growth and development of Islamic mandalas. With the case study of Sunan Bonang's mandala (Mandala Sunan Bonang) in Bonang Village, the researcher uses a historical approach and Islamic studies to reveal the socio-historical aspects of Mandala-based Islamic education activities. The text of Carita Sejarah Lasem, which is the primary source of this research, and other historiographical sources, was analyzed using the content analysis method. This study concludes that in the 15th-16th centuries AD, the mandala had an essential role as the basis of Islamic da'wah and education for the community, especially on the north coast of Java. The development of mandalas in several areas, which is exemplified by Sunan Bonang's mandala, also shows the active support of local rulers for the process of Islamization in Nusantara society.